82.9k views
0 votes
(6m5 + 3 – m3 – 4m) – (–m5 + 2m3 – 4m + 6)

2 Answers

2 votes
Your Answer is
7m5-3m3-3
(6m5 + 3 – m3 – 4m) – (–m5 + 2m3 – 4m + 6)-example-1
User Hollden
by
5.8k points
4 votes

Answer:
7m^5-3m^3-3

Explanation:

You can observe that you need to subtract the polynomial
(6m^5 + 3 - m^3 -4m) and the polynomial
(-m^5 + 2m^3- 4m + 6).

It is important the remember the multiplication of signs:


(+)(+)=+\\(-)(-)=+\\(+)(-)=-

Then, the first step is to distribute the negative sign:


(6m^5 + 3 - m^3 -4m)-(-m^5 + 2m^3- 4m + 6)=\\=6m^5 + 3 - m^3 -4m+m^5-2m^3+ 4m- 6

And finally you must add the like terms. Then:


=7m^5-3m^3-3

User Zikes
by
5.3k points